New generalized trapezoid type inequalities for complex functions defined on unit circle and applications - Budak, H.; Budak, H. (Institute of Mathematics, NAS of Ukraine, 2020)
UDC 517.5 We establish new generalized trapezoid type inequalities for complex functions defined on unit circle via the function of bounded variation and the functions satisfying H¨older type condition. Using these results, quadrature rule formula is also provided.